2008
DOI: 10.1002/jssc.200700486
|View full text |Cite
|
Sign up to set email alerts
|

Peptide profile of human acquired enamel pellicle using MALDI tandem MS

Abstract: The present study proposes a strategy for human in vivo acquired enamel pellicle (AEP) peptidome characterisation based on sequential extraction with guanidine and TFA followed by MALDI-TOF/TOF identification. Three different nanoscale analytical approaches were used: samples were subjected to tryptic digestion followed by nano-HPLC and mass spectrometry (MS and MS/MS) analysis. Undigested samples were analysed by LC-MS (both linear and reflector modes) and LC-MS/MS analysis, and samples were subjected to nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 43 publications
4
43
0
5
Order By: Relevance
“…However, in agreement with Gibbins et al (2014), blotting experiments showed that statherin adsorbed preferentially on more hydrophobic substrata. The more substantial statherin adsorption on hydrophobized silica surfaces is consistent with previous reports (Santos et al 2008;Vitorino et al 2008). This is explained by the prevalence of the hydrophobic interaction developed between the hydrophobic substrata and the C-terminal part of the protein which also has a hydrophobic character.…”
Section: Discussionsupporting
confidence: 91%
“…However, in agreement with Gibbins et al (2014), blotting experiments showed that statherin adsorbed preferentially on more hydrophobic substrata. The more substantial statherin adsorption on hydrophobized silica surfaces is consistent with previous reports (Santos et al 2008;Vitorino et al 2008). This is explained by the prevalence of the hydrophobic interaction developed between the hydrophobic substrata and the C-terminal part of the protein which also has a hydrophobic character.…”
Section: Discussionsupporting
confidence: 91%
“…The resulting peptides were extracted with trifluoroacetic acid/acetonitrile/water, and then analyzed by MALDI-TOF, using sinapinic acid as matrix on a micro MX linear and reflection TOF mass spectrometer (Waters, Milford, MA). Screening of the LC-MALDI plate was performed in the MS positive reflector mode, using 1200 laser shots at a collision energy of 2 kV with air as collision gas at a pressure of 2.610 À7 Torr (Vitorino et al, 2008). The spectra were processed and analyzed by the Global Protein Server Workstation (Applied Biosystems, Foster City, CA), which uses internal MASCOT software (Matrix Science, Boston, MA) for searching the peptide mass fingerprints and MS/MS data.…”
Section: Maldi-tof/tof-ms Analysismentioning
confidence: 99%
“…In addition, several of the ions arose from unknown proteins. Using our proposed methodology of on-plate digestion more than 100 different tryptic peptides were characterised (12). This led to the identification of 12 distinct salivary proteins.…”
mentioning
confidence: 99%